Same-Sex Intimate Partner Violence in Canada: Prevalence, Characteristics, and Types of Incidents Reported to Police Services - Whitehead, Jessica (Journal of interpersonal violence, 2021)
During the past 50 years, there has been an increase in research and programming initiatives focusing on the issue of heterosexual intimate partner violence (Het-IPV). In comparison, less attention has been paid to same-sex intimate partner violence (SS-IPV). Furthermore, of the existing research, the majority focuses on SS-IPV incidents in the United States which, due to social and legal differences, cannot yield an accurate picture of SS-IPV in Canada. This descriptive study sought to understand the prevalence, characteristics, and types of SS-IPV and Het-IPV within a Canadian context, with an emphasis on understanding the differences and similarities of incidents reported to police services. It explores the influences of heteronormativity and hegemonic masculinity on SS-IPV reporting and recognition. To assess this, data from Statistics Canada’s 2007–2011 Uniform Crime Reporting (UCR) Surveys were utilized. Participation in this survey is mandatory for all police services and, therefore, the sample used contains over 99% of incidents of IPV reported in Canada during the 4-year period (N = 346,565). The results indicate that 4% of incidents of intimate partner violence reported to the UCR involved people engaged in same-sex relationships. It demonstrates that SS-IPV incidents are similar to Het-IPV incidents in reported prevalence, and the findings also show that there are differences in the types of violations reported and several incident characteristics, including levels of victim injury, and the population density of the offense location. These findings can provide a foundation for future research and raise further questions about how SS-IPV is responded to by the criminal justice system after it has been reported to police services.